Independent Candidates in the Concurrent Regional Election in South Sulawesi: What is Independent and Why? - Rasyid Thaha; Haryanto Haryanto (Jurnal Ilmu Sosial dan Ilmu Politik, 2017)
Researchers in many countries consider that independent candidates aﬀect the quality of elections wherein independent candidates can enhance the consolidation of democracy within the context of political openness, bring about more competitive elections, and become an established pathway for alternative leadership ﬁgures. In Indonesia, these conclusions need to be further explored with the implementation of provisions regarding independent candidates in local elections. Therefore, the main objective of this research is to illustrate the political events involving each individual candidate based on questions of individual actions. The main questions relate to why candidates choose the path of an independent, what capital they have, why are independent candidates more inﬂuential than others, and what are the consequences of their presence for democracy in Indonesia. This paper concludes that the independent track is merely one of the means available, in addition to the party, in pursuing political oﬃce in local elections. There is no apparent footing relating to what independent candidates stand for. Moreover, there is yet to be an independent candidate who is truly a social activist wanting to promote alternative issues, a representative of interest groups, or a representative of classes in the local community. Independent candidates are a part of a Schumpeterian procedural logic which is merely for political elite circulation. To put it simply, there is nothing new and rejuvenating in the practices of local democracy in Indonesia.